Anteverted concha: A new ear deformational anomaly. (September 2015) - Schönauer, Fabrizio; Di Martino, Annalena; Gault, David T.
Abstract: Most auricular deformities involve the helix and the antihelix (Stahl's bar, lop and prominent ear); an isolated conchal deformity is uncommon in an otherwise normal ear. When a convexity rather than a concavity of the concha is present, it can be defined as "anteverted concha". The anteverted concha causes not only aesthetic but also functional problems. It may be so severe as to occlude the external auditory meatus. In a newborn ear amenable to moulding, anteverted concha can be treated non-surgically by splinting. If this time window has passed, then surgical excision of the conchal bulge can give good results in the adult. We present two such cases and their treatment.